PENGARUH SALURAN DISTRIBUSI DAN PERSONAL SELLING TERHADAP VOLUME PENJUALAN PT. BORWITA CITRA PRIMA SIDOARJO - andjarwati, tri; nur hakim, vicky (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRACTCurrent economic activity requires a serious effort in gaining market. marketing is a very important issue that is noticed by the company in order to grow and develop. In an effort to get a market share is needed marketing strategies, so the company can achieve its goals. In achieving the goals of the company it takes effort to maximize all the opportunities that exist to be profitable for the company. The purpose of this study is to determine the distribution channel variables and personal selling simultaneously or partially significant effect on the sales volume of PT.Borwita Citra Prima Sidoarjo and to know that the distribution channel variable is the variable that has the most dominant influence on sales volume PT.Borwita Citra Prima Sidoarjo. The data analysis technique used in this research is using multiple linear regression with correlation test, determination, f test and t test with questionnaire tool and interview with sample of 60 respondents. The test result of this research is got result of doubled linear regression calculation that is Y = - 0,099 + 0,357 X1 + 0,628 X2 where both of variable have positive influence and direction with dependent variable that is sales volume PT.Borwita Citra Prima Sidoarjo. Simultaneous test results obtained Fcount of 123.753 which means Fcount 123.753> Ftable 3.16, or can be seen from the level of significance 0,000 <0,05 (Î± = 5%). While partially obtained Thitung Distribution Channel (X1) = 2.855, ThitungPersonal Seling (X2) = 4,623, thus Thitung> Ttabel (2,00247). So the hypothesis that the variables Channel Distribution And Personal Selling simultaneously or partially significant effect on sales volume PT.Borwita Citra Prima Sidoarjo proved true. Variable Personal Selling (X2) has the most dominant influence on sales volume because it has the largest regression coefficient is 0.628 than other variables.Â Keywords: Distribution Channels, Personal Selling, Sales Volume